Image-Based Computational Modeling of the Human Circulatory and Pulmonary Systems Methods and Applications - Chandran, Krishnan B.; Udaykumar, H. S.; Reinhardt, Joseph M.; SpringerLink (Online service). (Boston, MA Springer US, 2011)
Image-Based Computational Modeling of the Human Circulatory and Pulmonary Systems provides an overview of the current modeling methods and applications enhancing interventional treatments and computer-aided surgery. A detailed description of the techniques behind image acquisition, processing and three-dimensional reconstruction are included. Techniques for the computational simulation of solid and fluid mechanics and structure interaction are also discussed, in addition to various cardiovascular and pulmonary applications. Engineers and researchers involved with image processing and computational modeling of human organ systems will find this a valuable reference.
Introduction -- Image Acquisition -- Image Processing and 3D Reconstruction -- Computational Techniques for Biological Fluids -- Computational Techniques for Biological Soft Tissue -- Fluid-Structure Interaction Algorithm Development -- Arterial Circulation and Disease Processes -- Biomechanics of AAA, Cerebral Aneurysms, and Vascular Grafts -- Fluid Mechanics for Interventions and Surgical Planning -- Computational Analysis of Lung Tissue and Airway Flow Dynamics -- Mechanical Valve Fluid Dynamics and Thrombus Initiation -- Aortic, Mitral, and Biological Prosthetic Valve Dynamics -- Micro-Scale Analysis of Blood Particles and Use of Multi-Scale Models -- Multi-Scale Modeling of Biological Soft Tissue.
Electronic reproduction.
Keywords: Cardiopulmonary system -- Simulation methods; Cardiopulmonary system -- Imaging -- Simulation methods; Electronic book